2022
DOI: 10.3390/medicina58050652
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of Serum Serotonin as a Screening Marker for Anxiety and Depression in Patients with Type 2 Diabetes

Abstract: Over time, studies have shown the importance of determining serotonin levels to diagnose somatic and psychiatric disorders. There are theoretical premises and practical ways to achieve a subtle correlation between the existence of comorbid psychiatric disorders and somatic diseases caused by the changes observed in serotonin levels. The present study, classified as retrospective and quantitative, provides evidence for determining the serotonin levels in patients with diabetes and anxiety or depression. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
(18 reference statements)
0
18
0
Order By: Relevance
“…In particular, studies have demonstrated an association between COVID-19 and depression. 33 , 34 , 35 It has also been reported that the serum serotonin levels inversely correlated with the degree of anxiety and depression 36 ; thus, decreased serotonin levels with disease progression may be one of the causes of depressive syndrome of COVID-19, although the cause and effect remain unclear. On the contrary, the role of serotonin in the gastrointestinal symptoms has also been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies have demonstrated an association between COVID-19 and depression. 33 , 34 , 35 It has also been reported that the serum serotonin levels inversely correlated with the degree of anxiety and depression 36 ; thus, decreased serotonin levels with disease progression may be one of the causes of depressive syndrome of COVID-19, although the cause and effect remain unclear. On the contrary, the role of serotonin in the gastrointestinal symptoms has also been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the aetiology of major depressive disorder (MDD) in recent decades has been referred to the pathophysiology of the serotonin system [24]. It has been reported that patients with MDD show lower level of serotonin in serum [17][18][19][20][21][22]. Serotonin concentration was significantly lower in the patients with severe atopic dermatitis, and there was an adverse relation between the serotonin concentration and the score of depression, the features not noticed in the control group [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients with MDD show lower level of serotonin in serum [17][18][19][20][21][22]. Serotonin concentration was significantly lower in the patients with severe atopic dermatitis, and there was an adverse relation between the serotonin concentration and the score of depression, the features not noticed in the control group [20,22]. However, there is no study on the effects of forest bathing on serotonin in serum in humans so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations